2013
DOI: 10.3906/bot-1211-16
|View full text |Cite
|
Sign up to set email alerts
|

Agrophysiological and biochemical properties associated with adaptation of Medicago sativa populations to water deficit

Abstract: Materials and methods Plant material and growth conditionsFour Moroccan alfalfa populations, Tafilalet 1 (Taf 1), Tafilalet 2 (Taf 2), Demnate (Dem), and Tata, were used in this study. Seeds were supplied by National Institute for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
3
18
1
Order By: Relevance
“…), in alfalfa (Farissi et al . ) and in sesame genotypes (Kadkhodaie et al . ) but the magnitude of the increase reportedly depended on the genotype and drought level.…”
Section: Discussionmentioning
confidence: 99%
“…), in alfalfa (Farissi et al . ) and in sesame genotypes (Kadkhodaie et al . ) but the magnitude of the increase reportedly depended on the genotype and drought level.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in water‐limited wheat root RWC may be a result of higher DW and length of faba bean roots actively competing for water in this treatment as greater biomass and diameter of roots are paramount traits optimizing water and nutrient acquisition ( Ho et al, 2005). In addition, low P concentration in roots and shoots of the intercropped wheat may be related to the decrease of the root RWC which is considered an indicator of plant water status and capacity to acquire nutrients from the soil as well as a determinant factor for the metabolic activity and survival of leaves ( Krouma , 2010; Farissi et al, 2013). The reduced wheat performance under intercropping and water limitation also coincided with increased rhizosphere soil electrical conductivity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that 'Ameristand 801S' exhibited high forage yield, which is similar to our results. Farissi et al (2013) measured the effect of three water deficit levels in terms of field capacity (FC) (25% FC, 50% FC, and 75% FC) on agro-physiological and biochemical properties of four perennial alfalfa populations of Moroccan origin. They found that DM reduction was very high compared with the optimal treatment (75% FC) and production loss increased with water shortage severity.…”
Section: Fourth Year Of Productionmentioning
confidence: 99%